Influence of human settlements factors on the spatial distribution patterns of traditional villages in Liaoning province - Guiqiao Tao; Xueming Li; Shenzhen Tian; Hang Li; Yishan Song (Humanities & Social Sciences Communications)
Abstract Traditional villages embody China’s long-standing farming culture and are the carriers for the inheritance and development of traditional culture in rural China. However, because of the continuous erosion of rural space due to China’s rapid urbanization, traditional villages are gradually declining and even disappearing. Protecting traditional villages has become a significant scientific problem in the implementation of the “Rural Vitalization Strategy” in the new era. The study of the spatial distribution pattern of traditional villages and its influencing factors is an important basis for formulating macro-protection policies for traditional villages in China. However, the existing literature is one-sided and subjectivity in revealing the influencing factors, making it difficult to form accurate and comprehensive protection policies. Employing the Gini coefficient, kernel density estimation, and the Geographically Weighted Regression (GWR) model, this study analyzes the impact of human settlements factors on the spatial distribution patterns of traditional villages in Liaoning province. Results can be summated as follows. (1) The spatial distribution of traditional villages in Liaoning exhibits a clustered pattern. (2) In terms of the geographical regional scale, the distribution is highly uneven and mainly concentrated in the western region of Liaoning. At the municipal scale, the distribution is relatively uneven and primarily located in the cities of Chaoyang, Jinzhou, Huludao, Panjin, Anshan, and Dalian. (3) The majority of traditional villages are distributed along the southwest–northeast axis of the standard deviation ellipse, which corresponds with the main mountain ranges of Liaoning. (4) The distribution density features a western continuous clustering, central and eastern scattered clustering, and edge clustering pattern. (5) The spatial distribution patterns of traditional villages in Liaoning are influenced by various human settlements factors, with spatial variation in the nature and intensity of the effects of these factors. (6) The natural factors of human settlements are the dominant factors in the spatial distribution patterns of traditional villages, while the humanistic factors of human settlements have a dual impact on these patterns. This paper presents novel ideas for the study of the spatial distribution pattern of traditional villages, scientific support for the development of the disciplines of rural geography and the geography of human settlements, and new scientific decision-making and theoretical support for the protection and utilization of traditional villages.